Resistance capability of indigenous and non-indigenous bacteria species on 3,4-dichoroaniline - Mohd Zaini, N. A.; Hanapiah, Munirah; Mustafa, Muskhazli; Zulkifli, Syaizwan Zahmir; Mohamat Yusuff, Ferdius @ Ferdaus; Ismail, Ahmad (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
3,4- dichloroaniline (3,4-DCA) is commonly be used in the chemical industry and it is also a by-product of aniline-derived herbicides such as diuron, linuron and propanil. However, 3,4-DCA exhibits higher toxicity than its parent compound and persistent in soils, water and groundwater. The aim of study was to investigate three TBT-resistant bacteria which are Klebsiella sp., Acinetobacter sp., Citrobacter sp. to evaluate their resistancy towards 3,4-DCA. Pseudomonas sp. isolated from non-TBT-polluted area was used as a positive control. Respiratory inhibitory activity of 3,4-DCA on three bacteria strains were assessed by employing MTT-bioassay. Results showed, Citrobacter sp. is the most tolerable bacteria amongst three strains with the IC50 value of 7.83 mg/L followed by Acinetobacter sp. (7.55 mg/L), Klebsiella sp. (7.09 mg/L) and Pseudomonas sp. (7.02 mg/L). Due to that, potential TBT-degrading bacteria, Klebsiella sp. is not preferable bacteria to degrade or utilize 3,4-DCA mainly because of the structure and resistancy bacteria itself. Thus, future studies are recommended in order to remediate this highly persistant compound in solving environmental problems associated contamination.